Arabyyah and Mexicana Co-Teaching-Learning Testimonios of Revolutionary Women: A Pedagogy of Solidarity. Issue 3 (3rd July 2019) - Hamzeh, Manal; Flores Carmona, Judith
Abstract: Manal, an Arabyyah feminist and Judith, a Mexicana feminista share our experience co-teaching a course titled Revolutionary Women and Decolonizing Pláticas Testimonios, at a university along the U.S.–Mexico borderlands. We employed pláticas testimonios pedagogies and methodologies and read the testimonios of Chicanas/Latinas and revolutionary women from Palestine and Egypt. Our pedagogy was transformed, as we enacted feminista reflexión via pláticas and femtoring, illuminating the challenges and possibilities of an emerging decolonizing pedagogy of solidarity.